Overlapping Primary and Secondary Syphilis in Human Immunodeficiency Virus (HIV) Patient - Nurul Laili Nahlia; Lita Setyowatie (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTCoinfection between syphilis and Human Immunodeficiency Virus (HIV) could have varied clinical manifestations. Overlapping of syphilis stages is accounted for 25% of cases, attributable to the defect of the cellular and humoral immune response. We reported 55 years old man who was sexually active since 25 years ago via genito-genital, genito-anal, genito-oral routes, had multiple sexual partners both male and female, seldom used condom, and always being the insertive. Dermatological examination revealed alopecia non-scarring, a painless solitary ulcer on the collum penis, also multiple erythematous macules, patches, and plaques all over the body. Spirochaeta sp. was found from the base of the ulcer with a darkfield microscope. Histopathology examination revealed secondary syphilis lesion. Venereal Disease Research Laboratory (VDRL) 1:16, Treponema Pallidum Haemagglutination test (TPHA) reactive, HIV Determine rapid test reactive, and CD4 (Cluster of Differentiation 4) T-cell count 111 cells/ µL. He was treated with a single dose of benzathine penicillin G 2,4 million units intramuscular and antiretroviral drugs. On sixth month evaluation, VDRL was non-reactive, and CD4 T-cell count 325 cells/µL. This case shows that overlapping clinical manifestations of primary and secondary syphilis on HIV patients could occur with a good general condition. Immediate treatment of antibiotics for syphilis and antiretroviral could improve the clinical and serological conditions.Keyword: primary syphilis, secondary syphilis, HIVCorrespondence: nurul.laili.nahlia@gmail.com